Perfectionism and well-being: A positive psychology framework - Suh, Hanna; Gnilka, Philip B; Rice, Kenneth G (Personality and individual differences, 2017)
AbstractGrounded in the tripartite model of perfectionism and previous empirical support, the current study explored qualitatively different types of perfectionists and their well-being. A total of 276 college students responded to measures of perfectionism, conscientiousness, neuroticism, and well-being. Latent Profile Analysis identified three distinct latent classes of perfectionists: adaptive, maladaptive, and non-perfectionists. Adaptive perfectionists exhibited highest levels of presence of meaning, subjective happiness, and life satisfaction; maladaptive perfectionists showed the highest levels of search for meaning. Findings call attention to the value of exploring the heterogeneity of perfectionists and their well-being.